USING RESTORATIVE PRACTICES TO TEACH AND UPHOLD DIGNITY IN AN AMERICAN SCHOOL DISTRICT - High, Anna (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
The protection and promotion of dignity is a foundational objective of restorative justice. Dignity-enhancing restorative justice practices, which are rooted in the traditional practices of Indigenous people groups, have been widely adopted in schools reactively, as a response to specific infractions. A growing number of schools are adopting restorative practices proactively, with a view to preventing misbehaviour by improving climate and strengthening relationships. This report from the Evanston / Skokie School District (K-8) in Illinois explores a cost-effective restorative practice implementation plan that focuses on volunteers and teachers partnering to introduce one key proactive practice, sharing circles, to classrooms. Using Donna Hicks’ “essential elements of dignity” as a framework, I argue that restorative circle initiatives are a simple and effective means of transforming school communities by acknowledging, promoting and honouring the dignity of students.